2008
DOI: 10.1016/j.worlddev.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Destructive Competition: Factionalism and Rent-Seeking in Iran

Abstract: Empirical evidence shows that countries richly endowed with natural resources like oil and gas tend to have slower economic growth than resource poor countries. The present paper focuses on rentseeking as a source of the "resource curse", using Iran as a case in point. Iran is an interesting case, both because it is a rentier economy in the oil rich Middle East, and because its political system is highly factionalized. The distortions from the factionalized political system are threefold. First, resources are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…which is equivalent to the Montalvo and Reynal-Querol index of polarization. In the resource-curse literature, several papers treat access to natural resources as an excludable but non-rivalrous public good, in which case ethnic polarization is likely to intensify rent-seeking competition (e.g., see Ross 2001;Acemoglu, Robinson, and Verdier 2004;Bjorvatn and Selvik 2008;Caselli and Cunningham 2009;Robinson and Torvik 2005 just to mention a few). The ultimate objective of rent-seeking competition may hence be to enable the winning group to gain access to power, which can then be sustained with the control of natural-resource rents 2 In their rent-seeking model, individuals are distributed in M groups that allocate resources (effort) to enhance the probability of success in appropriating the contested good and maximize their net benefits (given their probability of success, the anticipated utility related to their preferred outcome and the cost of rent-seeking effort; see Montalvo and Reynal-Querol 2005a, pp.…”
Section: R K Pmentioning
confidence: 99%
“…which is equivalent to the Montalvo and Reynal-Querol index of polarization. In the resource-curse literature, several papers treat access to natural resources as an excludable but non-rivalrous public good, in which case ethnic polarization is likely to intensify rent-seeking competition (e.g., see Ross 2001;Acemoglu, Robinson, and Verdier 2004;Bjorvatn and Selvik 2008;Caselli and Cunningham 2009;Robinson and Torvik 2005 just to mention a few). The ultimate objective of rent-seeking competition may hence be to enable the winning group to gain access to power, which can then be sustained with the control of natural-resource rents 2 In their rent-seeking model, individuals are distributed in M groups that allocate resources (effort) to enhance the probability of success in appropriating the contested good and maximize their net benefits (given their probability of success, the anticipated utility related to their preferred outcome and the cost of rent-seeking effort; see Montalvo and Reynal-Querol 2005a, pp.…”
Section: R K Pmentioning
confidence: 99%
“…Iran serves as an example where the experience may be driven by the behaviour of conflicting interest groups (Hodler, 2006 andBjorvatn andSelvik, 2008).…”
Section: -Figure 1 About Here-mentioning
confidence: 99%
“…First, the investment channel is explicitly addressed. Iran might be seen as an example where the experience could be driven by the behaviour of conflicting interest groups (Hodler, 2006 andBjorvatn andSelvik, 2008). Rent seeking in a highly fractionalised economy can lead to a waste of resources and can dampen economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Demands for interest rate cuts have not only led to increasing inflation, they have also resulted in panic in the Iranian stock exchange (Tait 2007). Ahmadinejad demonstrated that he had very little respect for economic experts when he purged the banks and insurance companies of their experienced employees and replaced them with his allies (Bjorvatn and Selvik 2008). The resignation of the Governor of the Central Bank of Iran, Ebrahim Sheibani, over reported discontent about being forced to reduce interest rates from 17 to 12 percent by the President was another sign of ongoing problems in the Iranian economy (New York Times 2007; Erdbrink 2008).…”
Section: Domestic Politics and Iranian Diversionary Behaviormentioning
confidence: 99%